Kajian atas Prinsip Tanggung Jawab Terbatas dan Doktrin Piercing the Corporate Veil Terhadap Perseroan Terbatas - Angelina Saraswaty; Hudi Yusuf (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The separation of a company's assets from the personal assets of its shareholders gives rise to the principle of limited liability, as regulated under Article 3 paragraph (1) of Law No. 40 of 2007 on Limited Liability Companies as amended by Law No. 6 of 2023, which restricts shareholders' liability to the value of shares they have paid in. However, this principle does not apply absolutely, as the law recognizes the doctrine of piercing the corporate veil, which allows judges to impose personal liability on shareholders, directors, or commissioners under certain circumstances, as stipulated in Article 3 paragraph (2) of the Company Law. The findings show that PT's legal entity status provides legal certainty in business relationships; however, limited liability protection may be set aside where the requirements for legal entity status have not been fulfilled, where bad faith is present, where shareholders are involved in unlawful acts, or where corporate assets are misused. The application of this doctrine in Indonesia still requires further refinement through jurisprudence to achieve a balance between protecting investors and protecting creditors or third parties.